Status Gizi , Activity Daily Living Berkaitan Kadar Gula Darah Lansia Diabetes Melitus - Ferdinan Yanto Malo; Ronasari Mahaji Putri; Ragil Catur Adi Wibowo (Buletin Kesehatan: Publikasi Ilmiah Bidang kesehatan, 2021)
DM elderly has increased from time to time. The nutritional status of the elderly who are not normal and low ADL is one of the things that associated with temporary blood glucose levels. The purpose was to determine the relationship nutritional status and ADL with blood sugar levels in patients with Type II DM in the elderly at X Health Center. The research design used cross sectional. The study population was 40 elderly with a total sample of 36 elderly. Samples were taken using simple random sampling technique. This study used a questionnaire and observation instruments. Data analysis using Fisher Exact test. The results of this study indicate that almost half of the elderly have nutritional status in the fat category. Most of the elderly have ADL in the less category. Almost half of the elderly have blood sugar when in the bad category and there is a relationship between nutritional status (p = 0.000) and ADL (p = 0.006) with blood sugar levels in elderly women with type II DM at X Health Center Malang City. It is hoped that further research will examine the role of the family in relation to nutritional status and ADL.